A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa